Discipline problems among secondary school students in Johor Bahru, Malaysia - Yahaya, Azizi; Ramli, Jamaluddin; Hashim, Shahrin; Ibrahim, Mohd. Ali; Raja Abd. Rahman, Raja Roslan; Yahaya, Noordin (EurojournalPublication, 2009)
The indiscipline problem in schools is ranked as a major problem among students of primary and secondary schools in Malaysia. Disruptive behavior is a concern to schools and parents and to fellow pupils, whose education may be adversely affected.Objective:The objectives of this study were to identify the level of students discipline problems and dominant factors attributing to the students discipline problems among the secondary school students in Johor in Malaysia.Material and Methods:The study was carried out to 90 discipline teachers from several secondary schools around Johor using questionnaires. The data collected were analyzed by Statistical Packages for Social Science (SPSS) in forms of frequency, percentage and mean value. The findings showed that the level of discipline problems among students was quitehigh especially for absenteeism problem.Results and Discussion:The results also showed that the students with family problems,always hung out with friends and others faced high level of discipline problems compared to students with no such problems. Some of the students with records in discipline problems showed that they did not faced any difficulties in learning as they passed in their examinations and the discipline problems did not depend on parents’ education background because it was not necessary for the students to have discipline Conclusions: Lastly, some recommendations also had been put forward as guidance to the research organization and future researches.